Soft‐Chemistry‐Assisted On‐Chip Integration of Nanostructured α‐Quartz Microelectromechanical System. Issue 3 (25th January 2021) - Jolly, Claire; Gomez, Andres; Sánchez‐Fuentes, David; Cakiroglu, Dilek; Rathar, Raïssa; Maurin, Nicolas; Garcia‐Bermejo, Ricardo; Charlot, Benoit; Gich, Martí; Bahriz, Michael; Picas, Laura; Carretero‐Genevrier, Adrian
Abstract: The development of advanced piezoelectric α‐quartz microelectromechanical system (MEMS) for sensing and precise frequency control applications requires the nanostructuration and on‐chip integration of this material on silicon material. However, the current quartz manufacturing methods are based on bonding bulk micromachined crystals on silicon, which limits the size, the performance, the integration cost, and the scalability of quartz microdevices. Here, chemical solution deposition, soft‐nanoimprint lithography, and top‐down microfabrication processes are combined to develop the first nanostructured epitaxial (100)α‐quartz/(100)Si piezoelectric cantilevers. The coherent Si/quartz interface and film thinness combined with a controlled nanostructuration on silicon–insulator–silicon technology substrates provide high force and mass sensitivity while preserving the mechanical quality factor of the microelectromechanical systems. This work proves that biocompatible nanostructured epitaxial piezoelectric α‐quartz‐based MEMS on silicon can be engineered at low cost by combining soft‐chemistry and top‐down lithographic techniques. Abstract : This study presents the first on‐chip chemical integration and nanostructuration of piezoelectric quartz microelectromechanical system (MEMS) resonators in the form of high‐quality cantilevers. These quartz‐based devices open the door to the development of biocompatible MEMS engineered from lead‐free piezoelectric oxide materials, providing high force and mass sensitivity while preserving the mechanical quality factor.